1) 2х + 15 = 3х - 11 2) 7 - 5х = х - 2
15 + 11 = 3х - 2х 7 + 2 = х + 5х
х = 26 6х = 9
х = 9 : 6
х = 1,5
- - - - - - - - - - - - - - - - - - - - - - - - - - - - - - - - - - - - - - -
3) 2(х - 3) = 3(2 - х) 4) -3(4 - х) = 2(х - 5)
2х - 6 = 6 - 3х -12 + 3х = 2х - 10
2х + 3х = 6 + 6 3х - 2х = 12 - 10
5х = 12 х = 2
х = 12 : 5
х = 2,4
aх² + bх + с = 0 - общий вид квадратного уравнения
б) 0,3х² - 7,5х = 0
Разделим обе части уравнения на 0,3
х² - 25х = 0
D = b² - 4ac = (-25)² - 4 · 1 · 0 = 625 - 0 = 625
√D = √625 = 25
х = (-b±√D)/2а
х₁ = (25-25)/(2·1) = 0/2 = 0
х₂ = (25+25)/(2·1) = 50/2 = 25
ответ: (0; 25).
- - - - - - - - - - - - - - - - - - - - - - -
а² - b² = (a + b)(a - b) - разность квадратов
г) 1/4х² - 25 = 0
0,25х² - 5² = 0
(0,5х)² - 5² = 0
(0,5х + 5)(0,5х - 5) = 0
0,5х + 5 = 0 и 0,5х - 5 = 0
0,5х = -5 0,5х = 5
х = -5 : 0,5 х = 5 : 0,5
х₁ = -10 х₂ = 10
ответ: (-10; 10).